Characterisation of radiogenic monoalkenes in Australian oils and condensate. (January 2022) - Boreham, Christopher J.; Jinadasa, Neel; Sohn, Jacob; Hong, Ziqing; Blake, Christopher
Highlights: Monoalkene content varies between 0.01 wt% and 22.3 wt% of the whole oil. Radiolytic n -alkenes show a distribution very similar to that of the n -alkanes. The unresolved complex mixture is dominated by an unresolved complex mixture. The carbon and hydrogen isotope values of n -alkenes and n -alkanes are very similar. Long oil residence time results in a near-equilibrium n -alkene isomer distribution. Abstract: Thirteen Australian oils and one condensate, covering oil reservoir ages from Mesoproterozoic to Early Cretaceous, show monoalkene contents varying from 0.01 to 22.3 wt% of the whole liquid. Radiolysis of saturated hydrocarbons is the most likely process leading to oils with high alkene contents. The major radiolytic component is an unresolved complex mixture (UCM). The bulk of the resolved alkene compounds are positional isomers of n -alkenes. Methyl branched and cyclohexyl alkenes are minor components. Internal n -alkene isomers have a trans configuration dominant over the cis isomer. The oil with the longest reservoir residence time shows the highest content of internal n -alkenes relative to terminal 1-alkenes as well as the highest trans / cis ratio, suggesting the extended time has resulted in rearrangement to near thermodynamic equilibrium of the congruent monoalkenes. The radiolytic monoalkenes in the Ordovician-reservoired oil with the highest alkene content is likely influenced by a higher probability of intermolecular interactions and different product pathways in a complex mixture. Here, the relative proportion of alkene mimics the relative abundance of n -alkanes, suggesting that radiolytic C–C bond cleavage is suppressed when the alkene/alkane ratio is elevated and that the preferred pathway of n -alkane radiolysis favours the production of terminal monoalkenes. Radiolysis of the alkane UCM together with crosslinking and branching of n -alkane-derived radiolysis products contribute to the higher relative proportion of the alkene UCM. The similar carbon and hydrogen isotopic ratios of the n -alkanes and n -alkenes supports a parent–daughter relationship.